Socio-demographic and clinical profile of elderly people with depression and the use of psychoactive drugs - Luiza Cantão; Leonardo Leão Kahey Fonseca; Talita Ingrid Magalhães Silva; Marcella de Oliveira; Valéria da Conceição de Oliveira; Richardson Miranda Machado (Rev Rene)
Objective: to know the socio-demographic and clinical profile of elderly patients with depressive disorders and the use of psychoactive drugs. Methods: it is a retrospective epidemiological study that analyzed 218 medical records of elderly patients in a Psychosocial Care Center in a period of 72 months. Results: it was observed that 67.9% of elderly men were predominantly those aged between 60 and 70 years. Alcohol was the most commonly used drug among men and tobacco among women, depression was the most frequent occurrence in both sexes. 53.7% were assisted at a health unit, and the predominant time of treatment was from 31 to 60 days (47.7%). The patients assisted by the family health teams were less frequent (10.5%). Conclusion: the cultural aspects of man’s role in society, easily accessible drugs (alcohol and tobacco) and the lack of information were the main factors related to depression and the use of drug by the elderly.